2016
DOI: 10.1007/s10641-016-0482-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative spatial ecology of sympatric adult muskellunge and northern pike during a one-year period in an urban reach of the Rideau River, Canada

Abstract: The reach of the Rideau River that flows through Ottawa, Ontario supports a recreational fishery for northern pike (Esox lucius) and muskellunge (Esox masquinongy). The reach is unique not only because such a vibrant esocid-based recreational fishery exists in an urban center, but that these two species co-occur. Typically, when these species occur sympatrically, northern pike tend to exclude muskellunge. To ensure the persistence of these esocid populations and the fisheries they support it is important to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Tags emitted short pulses at random, with a nominal delay of 60 s for 8 months during spring, summer, and fall. The transmitters shifted to a 90‐s ping rate during the four winter months to maximize tag life span during a period when Muskellunge tend to exhibit reduced movement (Miller and Menzel 1986; Younk et al 1996; Pankhurst et al 2016). We selected adults to obtain equal numbers of both sexes and a representative sample of adult Muskellunge lengths.…”
Section: Methodsmentioning
confidence: 99%
“…Tags emitted short pulses at random, with a nominal delay of 60 s for 8 months during spring, summer, and fall. The transmitters shifted to a 90‐s ping rate during the four winter months to maximize tag life span during a period when Muskellunge tend to exhibit reduced movement (Miller and Menzel 1986; Younk et al 1996; Pankhurst et al 2016). We selected adults to obtain equal numbers of both sexes and a representative sample of adult Muskellunge lengths.…”
Section: Methodsmentioning
confidence: 99%
“…Muskellunge are known to be territorial (Pankhurst et al. 2016), and Walleye tend to school and select for deeper water (Hartman 2009), possibly leading to higher retention rates after CWH addition. Smallmouth Bass have been observed to exhibit largescale movement patterns (Scott and Crossman 1973; Brown et al.…”
Section: Discussionmentioning
confidence: 99%
“…Muskellunge and Walleye tended to remain in a given habitat, while Smallmouth Bass showed a greater tendency to exchange between habitats. Muskellunge are known to be territorial (Pankhurst et al 2016), and Walleye tend to school and select for deeper water (Hartman 2009), possibly leading to higher retention rates after CWH addition. Smallmouth Bass have been observed to exhibit largescale movement patterns (Scott and Crossman 1973;Brown et al 2009) and therefore could have shown greater exchange rates in response to CWH when compared with Muskellunge and Walleye.…”
Section: Short-term Behavioral Responses Of Fishes To Cwh Additionmentioning
confidence: 99%
“…Pike can exhibit huge individual variation in habitat use, with documented long‐range movements of up to 300 km, but pike home range is generally much smaller, especially river‐dwelling fish (Skov et al, 2018). In rivers, their linear movements often range from 0 to 5 km, with individuals moving up to 37 km, with an approximate mean of 10 km, during the spawning season before swimming back to their starting location (Koed et al, 2006; Masters et al, 2005; Ovidio & Philippart, 2005; Pankhurst et al, 2016). In line with these findings, other studies on rivers that have shown that pike generally travel a few metres or kilometres around the stocking location, with movements of up to 15 km up and downstream (Cormont et al, 2020; Guillerault, Loot et al, 2018).…”
Section: Methodsmentioning
confidence: 99%